Novel m.15434C>A (p.230L>I) Mitochondrial Cytb Gene Missense Mutation Associated with Dilated Cardiomyopathy. (3rd July 2012) - Zarrouk Mahjoub, Sinda; Mehri, Sounira; Ourda, Fatma; Finsterer, Josef; Ben Arab, Saïda
Abstract : Background . Previously it has been shown that various types of hypertrophic and dilative cardiomyopathy (hCMP, dCMP) can be attributed to disturbed mitochondrial oxidative energy metabolism. Several studies described mutations in mitochondrial DNA-located genes encoding for subunits of respiratory chain complexes, including the cytochrome b gene (MT-CYB), causing CMPs. Methods and Results . In the present study the MT-CYB gene was analysed in 30 patients with hCMP, 40 patients with dCMP, and 50 controls for alterations. Altogether, 27 MT-CYB variants were detected. Twenty-four of them were single nucleotide polymorphisms defining common haplogroups. The variant m.15434C> A was found in a single patient with severe dCMP and assessed as novel mutation, since it was not found in healthy controls or available data sets, and was nonhaplogroup associated with Phylotree. This variant altered an amino acid (L230I) with a high interspecific amino acid conservation index (CI = 97.7 %) indicative of the functional importance of the residue. Conclusions . Though the L230I mutation seems to play a causative role for dCMP, prospective studies on yeast or transgenic mice models with defined mutation are warranted to study the pathogenetic impact of this mutation.